KORELASI BELIEFS DENGAN PEDAGOGICAL CONTENT KNOWLEDGE CALON GURU MATEMATIKA - Tina Sri Sumartini (Department of Mathematics Education, Universitas Kuningan, 2022)
Beliefs and Pedagogical Content Knowledge are important things for prospective mathematics teachers to have. The purpose of this study is to analyze the correlation of beliefs with Pedagogical Content Knowledge of prospective mathematics teachers. The research method used quasi-experimental with purposive sampling technique. The research sample is students majoring in Mathematics Education at Institut Pendidikan Indonesia. Data was collected by giving written tests and questionnaires which were then analyzed using Spearman correlation. The results of the study show that there is a correlation between beliefs and Pedagogical Content Knowledge of prospective mathematics teachers.